Child sexual abuse : the value of children’s testimonies and their influence on prosecutions and convictions. Cases of children aged 3½ to 14, referred to Iceland‘s Children´s House from 1998 to 2012 - Linzi Margaret Trosh 1988- (2016)
The main objective of this study was to examine what factors regarding children’s testimony had an influence on the prosecution and conviction of alleged sex offenders. The sample consists of 542 cases from 1998 to 2012 where there was reason to believe a child had been subjected to sexual abuse. The children were interviewed at Children’s House in Iceland. Factors regarding the children’s testimonies were obtained by an expert interviewer who analysed reports and video recordings of investigative interviews. To obtain information about cases that were prosecuted a researcher read through court files. Results showed that cases are more likely to be prosecuted when a child gives a detailed description of the alleged abuse and when cases involved children that were older than 9 years of age. Cases were three times more likely to be prosecuted when children gave a detailed description of the abuse itself. These finding suggest that when deciding to prosecute cases of alleged sexual abuse children are expected to disclose very detailed information of events when testifying. This may prove problematic for young children since they have age-related communication and language difficulties and are therefore not able to give a detailed description of events the same way older children can. It is therefore important that authority figures in the judicial system take children’s abilities into consideration when deciding to prosecute.